SELF REPORT MEASURE FOR BORDERLINE PERSONALITY TRAITS IN CLINICAL POPULATION - Butt, Mirrat Gul; Mahmood, Zahid; Saleem, Sadia (Journal of Postgraduate Medical Institute, 2017)
Objective: To develop an indigenous self-report measure for borderline personality traits in a clinical sample. Methodology: During the first phase, phenomenology was explored by conducting in-depth interviews of 15 diagnosed patients. The repeated and dubious responses were screened out that resulted in the production of a league table. Five experienced clinical psychologists and five psychiatrists validated the items and as a result, 33 items of the scale were retained out of 44 items. This preliminary study was conducted on 81 diagnosed participants (24 males and 57 females) who were selected through purposive sampling technique. All the participants were diagnosed by expert psychologists and psychiatrists. Results: Factor analysis revealed two factors namely mood liability and insecure dependence respectively. Significant positive correlation was found between Borderline personality traits scale (BPTS) and Zanirini borderline personality disorder scale (ZAN-BPDS). The internal consistency of the scale was excellent with Cronbach's alpha value of .87. Conclusion: The scale can be used on Pakistani population without any language or comprehension barrier.